Beginning programming with Python for dummies - Mueller, John, 1958- 4 0 16; 5 (Hoboken, NJ : John Wiley & Sons, 2014)
An introduction to the basics of Python, including getting started, dealing with errors, working with strings, and other related topics.
Includes index.
Adult;Adult.
Keywords: 2 -- 0; 6; Python (Computer program language);Computer programming.;Python (Computer language); 20; 2